The Limitation of Google Classroom as An Online Platform in EFL Teaching - Yuliana; Ohorella, Hayat M; Oratmangun, Emiliana; Sultan, Eva Lestari (JULIET: Journal of English Language and Literature, 2024)
Education is a crucial component of the process of constructing a nation. Education aims to transform the human mindset, fostering a more expansive and morally upright behavior. Furthermore, education is frequently referred to as the educational process. Information technology is a viable choice for structuring educational programs in the field of education. Web-based learning, utilizing the Internet as a medium, is a prevalent form of e-learning that is now being extensively explored by academic institutions. The Research Method section provides an in-depth analysis of the research methodology employed in this study. This text encompasses the examination of the research design, the subject and object of the study, the research instrument, the collecting of data, the analysis of data, and the verification of data for the study. According to Gay el.al (2006), descriptive research involves the analysis and description of factual information. The research process, as outlined by Gay et.al, involves several key processes. These include defining the research topic, doing a thorough assessment of existing literature, carefully selecting participants, collecting relevant data, analyzing and interpreting the data, and finally, reporting and evaluating the research findings. Objective: To ascertain the individuals who will be involved. Both assessments were conducted subsequently, once the pupils had acquired the necessary instructional content. The study aims to determine What are the constraints encountered when implementing online teaching using the Google Classroom Application during the third semester at the University of Muhammadiyah Sorong? This research employs a qualitative methodology that specifically examines empirical data collected in the field. The implementation of Google Classroom in EFL classes faces three obstacles: limited internet connection, insufficient interaction capabilities, and potential for cheating.